Design and Fabrication of Automatic Timetable Generator and its Application - Shubham Yadav; Omkar Pasalkar; Aniket Marne; Manisha P. Navale; Atharva Pawar (International Journal of Advanced Robotics and Automation Technology, 2023)
Making a schedule manually is exceedingly challenging in today's literate environment. Timetables must be made specifically for each branch and each year. It becomes quite chaotic, time-consuming, and labor-intensive to manually prepare the timetables. When a staff member needs to be substituted or is on leave, the process can occasionally become complicated. In our effort, we have developed a timetable-creation algorithm that will save a lot of time while lessen the workload and pressure on the employee. By using software to complete the task, much time is saved, and complex circumstances can also have schedules created. Additionally, it will prevent human error due to subject overlap and open positions. The creation of timetables is a difficult and time-consuming task, but it is essential to the coordination of many operations in educational institutions. The development of automatic timetable generation technologies has significantly streamlined this procedure, lowering labour costs and increasing productivity. This study paper offers a thorough examination and critique of the piece named "Automatic Timetable Generator." The fundamental ideas, methods, benefits, and difficulties of automatic timetable creation systems are examined in this work. It also examines how these systems affect educational institutions and identifies possible topics for additional study and development.
Keywords: Automated Timetable; Genetic Algorithm; Soft And Hard Constrains